Mathphy 7
Mathphy 7
Mathphy 7
1. Complex variables
√
A complex variable z may be expressed as z = x + iy where i = −1, and x and
y are real values. In this form, x is known as real part of z whereas y is known
as imaginary part of z. Usually the real part x is denoted as Rz or R(z) and the
imaginary part y as Iz or I(z). In the graphical representation of a complex variable,
its real part is taken on abscissa whereas the imaginary part is taken on ordinate
(Figure 1). In terms of real values, a complex variable z = x + iy is defined as an
ordered pair (x, y) of real values x and y. Two complex numbers are said to be
equal if and only if their real as well as imaginary parts are equal, separately. For
example, the two complex numbers (x1 , y1 ) and (x2 , y2 ) are equal only when x1 = x2
and y1 = y2 .
z
b
a x
Figure 1: Graphical representation of a complex number z = a + ib. Here, a and b are real
values taken on the x and y axes, respectively.
1
2 Mathematical Physics
p
The non-negative quantity r = x2 + y 2 is known as the modulus of z. The real
quantity θ is known as the argument of z and is denoted by arg z.
1. Modulus of the sum of two complex numbers z1 and z2 can never exceed the
sum of their individual moduli. That is,
2. Modulus of the difference of two complex numbers z1 and z2 can never be less
than the difference of their individual moduli. That is,
|z1 − z2 | ≥ (|z1 | − |z2 |)
As an example, √
let us take z1 = 5+4i √
and z2 = 3+2i so that z1 z2 √
= 7+22i. Now
we have |z1 | = 41 = 6.403, |z2 | = 13 = 3.605 and |z1 z2 | = 533 = 23.08,
showing that |z1 z2 | = |z1 ||z2 |.
It can be generalized as
2.1 Addition
Addition of two complex numbers z1 = (x1 , y1 ) and z2 = (x2 , y2 ) is defined as
= (x1 + x2 , y1 + y2 )
2.2 Subtraction
Subtraction of a complex number z2 = (x2 , y2 ) from another complex number z1 =
(x1 , y1 ) is defined as
= (x1 − x2 , y1 − y2 )
2.3 Multiplication
Multiplication of two complex numbers z1 = (x1 , y1 ) and z2 = (x2 , y2 ) is defined as
= (x1 x2 − y1 y2 , x1 y2 + x2 y1 )
4 Mathematical Physics
2.4 Division
Division of a complex number z1 = (x1 , y1 ) by another complex number z2 = (x2 , y2 )
is defined as
z1 x1 + iy1
=
z2 x2 + iy2
so that
q
r= x2 + y 2 and θ = tan−1 (y/x)
This represents the polar form of a complex number z. The distance r from the
origin, which is always positive, is the modulus of the complex number and the
angle θ is the argument of the complex number z. Complex conjugate of z is
Exercise 1: For a complex variable z, resolve ln(z) into real and imaginary parts.
z = r eiθ
where
q
r= x2 + y 2 and θ = tan−1 (y/x)
Complex Numbers and Functions 5
Thus, we have
1
ln(z) = ln(r eiθ ) = ln(r) + iθ = ln(x2 + y 2 ) + i tan−1 (y/x)
2
It gives the real part (1/2) ln(x2 + y 2 ) and imaginary part tan−1 (y/x).
5 + 4i = a2 − b2 + i2ab
Thus,
2
a 2 − b2 = 5 ab = 2 and a=
b
and therefore,
4
− b2 = 5 b4 + 5b2 − 4 = 0
b2
giving √
2−5 + 41
b = = 0.702
2
Here, we have not taken negative sign, as it gives negative value of b2 which is of no
use. Thus, b = 0.837 and a = 2/0.837 = 2.389. Therefore, we have
√
5 + 4i = 2.389 + i0.837
√
(ii) Let 7 − 6i = a − ib. Squaring on both sides, we have
7 − 6i = a2 − b2 − i2ab
Thus,
3
a 2 − b2 = 7 ab = 3 and a=
b
and therefore,
9
− b2 = 7 b4 + 7b2 − 9 = 0
b2
giving √
2−7 + 85
b = = 1.110
2
Here, we have not taken negative sign, as it gives negative value of b2 which is of no
use. Thus, b = 1.053 and a = 3/1.053 = 2.849. Therefore, we have
√
7 − 6i = 2.849 − i1.053
6 Mathematical Physics
√
(iii) Let i = a + ib. Squaring on both sides, we have
i = a2 − b2 + i2ab
Thus,
a 2 − b2 = 0 ab = 1/2
giving
1
a = b = ±√
2
Hence, we have
√ 1
i = ± √ (1 + i)
2
√
(iv) Let −i = a − ib. Squaring on both sides, we have
−i = a2 − b2 − i2ab
Thus,
a 2 − b2 = 0 ab = 1/2
giving
1
a = b = ±√
2
Hence, we have
√ 1
−i = ± √ (1 − i)
2
Solution: We have real part x = 1 − cos α and imaginary part y = sin α. Therefore,
sin α π α
tan θ = = cot α/2 = tan −
1 − cos α 2 2
Hence,
π α
θ= −
2 2
Thus,
αh π α π α i
1 − cos α + i sin α = 2 sin cos − + i sin −
2 2 2 2 2
Complex Numbers and Functions 7
Y
qP(x, y)
z = x + iy
θ X
O
P2
z2
+ z2
z1
z2 z=
P1 K
z1
X
O L N
8 Mathematical Physics
We have ON = OL + LN = x1 + x2 and NP = NK + KP = y1 + y2
The coordinates of P are (x1 + x2 , y1 + y2 ) and it represents the complex number
z = (x1 + x2 ) + i(y1 + y2 ) = (x1 + iy1 ) + (x2 + iy2 ) = z1 + z2
Thus, the point P represents the sum of the complex numbers z1 and z2 , such that
|z1 + z2 | = OP and amp(z1 + z2 ) = 6 XOP
Y
P2
z2
P1
z1
X
O M L
z
=
z1
-z2
−
Q
z2
P
N
R
Complex Numbers and Functions 9
Thus, the point P represents the difference z1 − z2 of the complex numbers, such
that
|z1 − z2 | = OP and arg(z1 − z2 ) = 6 XOP
P2
2
r1 r
r2
θ1
P1
θ2
θ1 r1 X
O A
Since z1 z2 = r1 r2 ei(θ1 +θ2 ) , our aim is to find a point whose modulus is r1 r2 and
argument is (θ1 + θ2 ).
Take OA = 1 along the real axis (Figure 5). Construct △AOP1 . At point P2
draw a line P2 P, such that 6 OAP1 = 6 OP2 P. Draw a line OP, such that 6 P2 OP =
θ1 . Now, △OP2 P is similar to the △AOP1 . Therefore,
OP OP2 OP r2
= or = or OP = r1 r2
OP1 OA r1 1
Now,
6 AOP = 6 AOP2 + 6 P2 OP = 6 AOP2 + 6 AOP1 = θ2 + θ1
Hence, the product of two complex numbers z1 and z2 is represented by the point P,
such that (i) |z1 z2 | = r1 r2 = |z1 ||z2 |, and (ii) argument (z1 z2 ) = θ1 + θ2 = argument
(z1 ) + argument (z2 ).
10 Mathematical Physics
Since z1 /z2 = r1 /r2 ei(θ1 −θ2 ) , our aim is to find a point whose modulus is r1 /r2 and
argument is (θ1 − θ2 ).
Y
P1
r1 P2
r2
P
r1 /r2
θ1 θ2
X
O A
Figure 6: Division of z1 by z2 .
Take OA = 1 (Figure 6). From point A, draw a line AP, such that 6 OAP =
6 OP2 P1 . Draw line OP, such that 6 AOP = 6 P2 OP1 . Now, △ OAP is similar to △
OP2 P1 . Thus, we have
OP OP1 OP r1 r1
= or = or OP =
OA OP2 1 r2 r2
6 AOP = 6 P2 OP1 = 6 AOP1 − 6 AOP2 = θ1 − θ2
Note: In the text, some times, (cos θ + i sin θ) would be abbreviated as cisθ.
5. De Moivre’s theorem
Statement of De Moivre’s theorem is as the following:
(A) If n is an integer, positive or negative, then
(cos θ + i sin θ)n = cos nθ + i sin nθ
Complex Numbers and Functions 11
(B) If n is a fraction, positive or negative, then one of the values of (cos θ + i sin θ)n
is cos nθ + i sin nθ
Proof (i) When n is a positive integer. Let us define cis θ = cos θ + i sin θ. By
multiplication, we have
cis θ1 cis θ2 = (cos θ1 cos θ2 − sin θ1 sin θ2 ) + i(sin θ1 cos θ2 + cos θ1 sin θ2 )
Further,
cis θ1 cis θ2 cis θ3 = cis (θ1 + θ2 )cis θ3 = [cos(θ1 + θ2 ) cos θ3 − sin(θ1 + θ2 ) sin θ3 )]
Putting θ1 = θ2 = . . . = θn = θ, we have
Here, we have applied the above case (i). On multiplying and dividing by (cos mθ −
i sin mθ), we have
Exercise 4: Simplify
Solution: We have
(cos 2θ + i sin 2θ)−2 = [(cos θ + i sin θ)2 ]−2 = (cos θ + i sin θ)−4
Thus, we have
Exercise 5: Prove that (1+cos θ+i sin θ)n +(1+cos θ−i sin θ)n = 2n+1 cosn (θ/2) cos(nθ/2).
and
sin θ 2 sin θ/2 cos θ/2
tan α = = = tan θ/2 α = θ/2
1 + cos θ 1 + 2 cos2 θ/2 − 1
Thus, the LHS is
1
Exercise 6: If 2 cos θ = x + x prove that
1 x2n + 1 cos nθ
(i) 2 cos rθ = xr + (ii) =
xr x 2n−1 +x cos(n − 1)θ
Solution: We have
1
x+ = 2 cos θ x2 − 2x cos θ + 1 = 0
x
√
2 cos θ ± 4 cos2 θ − 4
x= = cos θ ± i sin θ
2
(i) Taking positive sign, we have
On addition, we have
1
xr + = (cos rθ + i sin rθ) + (cos rθ − i sin rθ) = 2 cos rθ
xr
(ii) We have
Exercise 7: Find the cube roots of (i) 1, (ii) (-1), (iii) i and (iv) (-i).
(ii) Let
(iii) Let
h (4n + 1)π (4n + 1)π i1/3
x = (i)1/3 = (cos π/2 + i sin π/2)1/3 = cos + i sin
2 2
(4n + 1)π (4n + 1)π
= cos + i sin
6 6
where n = 0, 1, 2. Thus, three roots of i are
π π 5π 5π 9π 9π
cos + i sin ; cos + i sin cos + i sin
6 6 6 6 6 6
√ √
3 1 3 1
+i ; − +i ; −i
2 2 2 2
These are 3 cube roots of i.
(iv) Let
h (4n − 1)π (4n − 1)π i1/3
x = (−i)1/3 = [cos(−π/2) + i sin(−π/2)]1/3 = cos + i sin
2 2
(4n − 1)π (4n − 1)π
= cos + i sin
6 6
where n = 0, 1, 2. Thus, three cube roots of −i are
π π 3π 3π 7π 7π
cos − i sin ; cos + i sin cos + i sin
6 6 6 6 6 6
√ √
3 1 3 1
−i ; i; − −i
2 2 2 2
These are 3 cube roots of (−i).
Remark: For example, q-th roots of 5, -5, 5i, −5i can be calculated as:
16 Mathematical Physics
Exercise 8: Find the squaree roots of (i) 1, (ii) (-1), (iii) i and (iv) (-i).
x = (1)1/2 = (cos 0 + i sin 0)1/2 = (cos 2nπ + i sin 2nπ)1/2 = cos nπ + i sin nπ
1; −1
(ii) Let
i −i
(iii) Let
" #1/2
1/2 1/2 (4n + 1)π (4n + 1)π
x = (i) = (cos π/2 + i sin π/2) = cos + i sin
2 2
1 1 1 1
√ +i √ ; −√ − i √
2 2 2 2
Complex Numbers and Functions 17
(iv) Let
" #1/2
(4n − 1)π (4n − 1)π
x = (−i)1/2 = [cos(−π/2) + i sin(−π/2)]1/2 = cos + i sin
2 2
1 1 1 1
√ −i √ ; −√ + i √
2 2 2 2
These are 2 square roots of (−i).
= (cosn θ − n
C2 cosn−2 θ sin2 θ + n
C4 cosn−4 θ(i sin θ)4 + . . .)
18 Mathematical Physics
cos nθ = cosn θ − n
C2 cosn−2 θ sin2 θ + n
C4 cosn−4 θ sin4 θ − . . . (1.1)
and
n
sin nθ = C1 cosn−1 θ sin θ − n C3 cosn−3 θ sin3 θ + n C5 cosn−5 θ sin5 θ − . . . (1.2)
√ p
Replacing every sin θ by 1 − cos2 θ in equation (1.1) and every cos θ by 1 − sin2 θ
in equation (1.2), we get the required expansions of cos nθ and sin nθ.
Dividing equation (1.2) by equation (1.1), we get
Exercise 9: Expand sin 5θ, cos 5θ, tan 5θ in powers of sin θ, cos θ, tan θ, respectively.
cos 5θ + i sin 5θ = cos5 θ + 5 C1 cos4 θ(i sin θ) + 5 C2 cos3 θ(i sin θ)2
+ 5 C3 cos2 θ(i sin θ)3 + 5 C4 cos θ(i sin θ)4 + 5 C5 (i sin θ)5
= cos5 θ + 5i cos4 θ sin θ − 10 cos3 θ sin2 θ − i10 cos 2 θ sin3 θ + 5 cos θ sin4 θ + i sin5 θ
This is the required expression for cos 5θ. Equating the imaginary part on two sides
of equation, we have
1 1 1 1
+ 8 C5 z 3 5
+ 8 C6 z 2 6 + 8 C7 z 7 + 8 C8 8
z z z z
We know that n Cr = nC
n−r . Therefore
1 1 1 1
(2 cos θ)8 = z 8 + + 8
C 1 z 6
+ + 8
C 2 z 4
+ + 8
C 3 z 2
+ + 8 C4
z8 z6 z4 z2
= (2 cos 8θ) + 8(2 cos 6θ) + 28(2 cos 4θ) + 56(2 cos 2θ) + 70
Thus,
20 Mathematical Physics
1
cos8 θ = [cos 8θ) + 8 cos 6θ + 28 cos 4θ + 56 cos 2θ + 35]
128
1 1 1
z+ = 2 cos θ z− = 2i sin θ zp − = 2i sin pθ
z z zp
Therefore,
1 7 1 3 1 4 1 3 1 3
(2i sin θ)7 (2 cos θ)3 = z − z+ = z− z− z+
z z z z z
1 4 2 1 3 4 1 3 1
= z− z − 2 = z 4 − 4z 2 + 6 − 2 + 4 z 6 − 3z 2 + 2 − 6
z z z z z z
1 1 1 1 1
= z 10 − − 4 z 8
− + 3 z 6
− + 8 z 4
− − 14 z 2
−
z 10 z8 z6 z4 z2
= 2i sin 10θ − 4(2i sin 8θ) + 3(2i sin 6θ) + 8(2i sin 4θ) − 14(2i sin 2θ)
Thus,
1
sin7 θ cos3 θ = − [sin 10θ − 4 sin 8θ + 3 sin 6θ + 8 sin 4θ − 14 sin 2θ]
29
x2 x3
ex = 1 + x + + + ...
2! 3!
Similarly, the exponential function of a complex variable z(= x + iy) is expressed as
z2 z3
ez = 1 + z + + + ...
2! 3!
Exercise 12: For a complex variable z(= x + iy) show that ez = ex (cos y + i sin y).
Solution: We have
(iy)2 (iy)3 (iy)4 (iy)5
ez = ex+iy = ex eiy = ex 1 + iy + + + + + ...
2! 3! 4! 5!
h y2 y4 y3 y5 i
= ex 1− + − ... + i y − + − . . . = ex (cos y + i sin y)
2! 4! 3! 5!
Complex Numbers and Functions 21
10.1 Properties
1. Circular functions are periodic: sin z and cos z are periodic functions having
a real period of 2π whereas tan z, cot z have a period of π. That is sin z =
sin(2π + z), cos z = cos(2π + z), tan z = tan(π + z), cot z = cot(π + z).
2. Even and odd functions: cos z and sec z are even functions whereas sin z and
cosecz are odd functions. That is cos(−z) = cos z; sin(−z) = − sin z.
3. Euler’s theorem eiz = cos z + i sin z:
We know series expansions
z 2 z 4 62 z 3 z 5 72
cos z = 1 − + − + ... and sin z = z − + − + ...
2! 4! 6! 3! 5! 7!
The series expansion of eiz is
(iz)2 (iz)3 (iz)4 (iz)5 (iz)6 (iz)7
eiz = 1 + (iz) + + + + + + + ...
2! 3! 4! 5! 6! 7!
z2 z3 z4 z5 z6 z7
= 1 + (iz) − −i + +i − −i + ...
2! 3! 4! 5! 6! 7!
z 2 z 4 62 z 3 z 5 72
= 1− + − + ... + i z − + − + ...
2! 4! 6! 3! 5! 7!
= cos z + i sin z
where z is real or comlex. This is proof of Euler’s theorem.
ex + e−x 2 2
coth x = sechx = cosechx =
ex − e−x ex + e−x ex − e−x
22 Mathematical Physics
11.2 Formulas
1 1 + z
(iii) tanh−1 z = ln
2 1−z
eu − e−u
z = sinh u = eu − e−u = 2z e2u − 2zeu − 1 = 0
2
√
u 2z ± 4z 2 + 4 p
e = = z ± z2 + 1
2
Taking positive sign, we have
p p
eu = z + z2 + 1 or u = sinh−1 z = ln[z + z 2 + 1]
eu + e−u
z = cosh u = eu + e−u = 2z e2u − 2zeu + 1 = 0
2
Complex Numbers and Functions 23
√
u 2z ± 4z 2 − 4 p
e = = z ± z2 − 1
2
Taking positive sign, we have
p p
eu = z + z2 − 1 or u = cosh−1 z = ln[z + z 2 − 1]
eu − e−u e2u − 1
z = tanh u = = z(e2u + 1) = e2u − 1
eu + e−u e2u + 1
1+z 1 1 + z
e2u (1 − z) = 1 + z e2u = u = tanh−1 z = ln
1−z 2 1−z
Exercise 14: Separate real and imaginary parts of (i) sin(x + iy), (ii) cos(x + iy),
(iii) tan(x + iy)
Solution: We have
(i) sin(x + iy) = sin x cos iy + cos x sin iy = sin x cosh y + i cos x sinh y
(ii) cos(x + iy) = cos x cos iy − sin x sin iy = cos x cosh y − i sin x sinh y
sin 2x
Therefore, α=
cos 2x + cosh 2y
On subtraction, we have
sin(x + iy) sin(x − iy)
2iβ = tan(x + iy) − tan(x − iy) = −
cos(x + iy) cos(x − iy)
24 Mathematical Physics
sin(x + iy) cos(x − iy) − sin(x − iy) cos(x + iy) 2 sin 2iy
= =
cos(x + iy) cos(x − iy) cos 2x + cos 2iy
2i sinh 2y
=
cos 2x + cosh 2y
sinh 2y
Therefore, β=
cos 2x + cosh 2y
Hence,
sin 2x sinh 2y
tan(x + iy) = +i
cos 2x + cosh 2y cos 2x + cosh 2y
Exercise 15: Separate real and imaginary parts of (i) sinh(x + iy), (ii) cosh(x + iy),
(iii) tanh(x + iy)
Solution: We have
(i) sinh(x + iy) = −i sin i(x + iy) = −i sin(ix − y) = −i[sin ix cos y − cos ix sin y]
= −i[i sinh x cos y − cosh x sin y] = sinh x cos y + i cosh x sin y
(ii) cosh(x + iy) = cos i(x + iy) = cos(ix − y = cos ix cos y + sin ix sin y
= cosh x cos y + i sinh x sin y
(iii) Let α + iβ = tanh(x + iy) = −i tan i(x + iy) = −i tan(ix − y)
then α − iβ = tanh(x − iy) = −i tan i(x − iy) = −i tan(ix + y)
On addition of these two expressions, we have
h sin(ix − y) sin(ixz + y) i
2α = −i[tan(ix − y) + tan(ix + y)] = −i +
cos(ix − y) cos(ix + y)
h sin(ix − y) cos(ix + y) + sin(ix + y) cos(ix − y) i h 2 sin 2ix i
= −i = −i
cos(ix − y) cos(ix + y) cos 2ix + cos 2y
sinh 2x
Therefore, α=
cosh 2x + cos 2y
On subtraction, we have
sin(ix + y) sin(ix − y)
2β = tan(ix + y) − tan(ix − y) = −
cos(ix + y) cos(ix − y)
sin(ix + y) cos(ix − y) − sin(ix − y) cos(ix + y) 2 sin 2y
= =
cos(ix + y) cos(ix−) cos 2ix + cos 2y
2 sin 2y
=
cosh 2x + cos 2y
sin 2y
Therefore, β=
cosh 2x + cos 2y
Hence,
sinh 2x sin 2y
tanh(x + iy) = +i
cosh 2x + cos 2y cosh 2x + cos 2y
Complex Numbers and Functions 25
ew+2inπ = ew e2inπ = ew = z
ln(z) = w + 2inπ
It shows that logarithm of a complex number has an infinite number of values, and
is therefore, a multi-valued function.
The general value of logarithm of z is written as Ln (z) (beginning with capital
L) so as to distinguish from its principal value written as ln (z). This principal value
is obtained by putting n = 0 in general value.
Solution: We have
We have
1
= ln(x2 + y 2 ) + i[2nπ + tan−1 (y/x)]
2